Parasitoid Causes Cascading Effects on Plant-Induced Defenses Mediated Through the Gut Bacteria of Host Caterpillars - Wang, Jie; Mason, Charles J.; Ju, Xueyang; Xue, Rongrong; Tong, Lu; Peiffer, Michelle; Song, Yuanyuan; Zeng, Rensen; Felton, Gary W. (Frontiers in Microbiology, 2021)
Koinobiont endoparasitoid wasps whose larvae develop inside a host insect alter several important facets of host physiology, potentially causing cascading effects across multiple trophic levels. For instance, the hijacking of the host immune responses may have effects on how insects interact with host plants and microbial associates. However, parasitoid regulation of insect-plant-microbiome interactions are still under studied. In this study, we used the fall armyworm (FAW), Spodoptera frugiperda, and the braconid parasitoid Cotesia marginiventris to evaluate impacts of parasitism on the gut microbiome of FAW larvae, and respective maize plant defense responses. The level of reactive oxygen species (ROS) and microbial community in larval gut underwent significant changes in response to parasitism, leading to a significant reduction of Enterococcus, while elevating the relative abundance of Pseudomonas. FAW with parasitism had lower glucose oxidase (GOX) activity in salivary glands and triggered lower defense responses in maize plants. These changes corresponded to effects on plants, as Pseudomonas inoculated larvae had lower activity of salivary GOX and triggered lower defense responses in maize plants. Our results demonstrated that parasitism had cascading effects on microbial associates across trophic levels, and also highlighted that insect gut bacteria may contribute to complex interrelationships among parasitoids, herbivores, and plants.